Women’s Language Features in Summer McKeen’s Vlogs - Andriani, Ketut (Humanis, 2018)
The title of this study is Women’s Language Features in Summer McKeen’s Vlogs. This study is mainly aimed to find out and describe women’s language features found in Summer McKeen’s vlogs and to find out and explain the functions of women’s language in Summer McKeen’s vlogs. This study used Summer McKeen’s video blog as the data source. The data of this study were collected by using library research method by collecting the words or phrases uttered in Summer McKeen’s vlogs. The words found in the utterance indicated women’s language features. The collected data were organized into classification of women’s language features and the function of women’s language descriptively analyzed based on the theories applied in this study. The theories applied in this study were mainly based on the theory of women language proposed by Lakoff (1975). The findings showed that the features of women’s language found in Summer McKeen’s vlogs were lexical hedges filler, tag question, rising intonation on declaratives, empty adjectives, precise color terms, intensifiers, hypercorrect grammar, super polite forms, avoidance of strong swear words, and emphatic stress. Moreover, the findings also found that the functions of women’s language were to show uncertainty, to intensify or emphasize an utterance, to get response, to express feeling and to soften an utterance.